(Dis)connection between sports development and high-performance in Brazilian sports policies - Moretti de Souza, J. V.; Zamboni, K. J.; de Oliveira Santos, T.; Mezzadri, F. M. (International Journal of Sports Science & Coaching, 2025)
The transition from sports development to high-performance is a topic that is present in the academic literature. However, there is a gap regarding the participation in government programs, representation of clubs and school competitions during development, and the reflection of these actions in high performance. Therefore, this study aimed to evaluate if the participation in listed actions can influence the receipt of government incentives in athlete's careers. A questionnaire was used to collect responses from high-performance Brazilian athletes, asking about the moment of sports development. The main results show that representing sports clubs increases the chance of receiving more resources, and, as a proxy, being more successful, in a career, whereas competing in school competitions and participating in government programs during development decreases the chance of receiving higher amounts. The results highlight the disconnection between Brazilian sports policies from a talent development point of view, with the need to adapt these policies to improve the chance of better results.